Spectrophotometric Assay of phenylphrine hydrochloride Viacuopling with Diazotised p-Nitroaniline, Application toPharmaceutical Preparation - Alghany K. lbraheem, Abed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Simple, sensitive and reproducible spectrophotometric method was developed in aqueous medium and applicated for the estimation of pheylephrine hydrochloride in nasal drop and tussilet syrup. The method is based on the formation of orange coloured azo dye from the coup I ing of pheylephrine hydrochloride (PPH) with diazotised p-nitroaniline in alkaline medium of sodium hydroxide and sodium carbonate. The intensity of absorbance for the resulting orange azao-dye was measured at 490 nm in sodium hydroxide and at 487 nm in sodium carbonate. Beer's law was obeyed in the concentration ranges of 10-200µg of PPH (r2=0.9988) in sodium hydroxide and of 10-lSOµg of PPH (r2=0.9981) in sodium carbonate in a final volume of 10 ml, with molar absorptivity of l.14xl04 1.mor1 .cm-1 in sodium hydroxide and l.98x 104 l.mor1 .cm-1 in sodium carbonate. The results demonstrated that the procedure is accurate, precise and reproducible (relative standard deviation was+0. 8 to + 1.53% and relative error was - 1.6 to+ 1.7% depending on the concentration level of (PPH), while being simple, cheap and less time consuming. The azo-dye was stable for more than 2 hours in sodium carbonate and for 13 hours in sodium hydroxide .The proposed method was successfully applied for the dtermination of phenylephrine hydrochloride in pharmaceutical nasal drops and tussilet syrup formulations.